Super‐lift boost converters. Issue 7 (1st July 2014) - Luo, Fang Lin; Ye, Hong
Abstract : Voltage lift technique has been successfully employed in design of DC/DC converters, for example, four series Luo‐converters. However, the voltage transfer gain increases stage‐by‐stage in arithmetic progression. Super‐lift converters largely enhance the voltage transfer gain, which increases stage‐by‐stage in geometric progression. It effectively enhances the voltage transfer gain in power series. This study introduces a novel approach – modified super‐lift converters that implements the super‐lift operation as well, its voltage transfer gain increases stage‐by‐stage also in geometric progression.